A Comparative Study of Social Problems in Surah An-Nur in Light of Ahkam Al-Quran by Al-Jassas and Ahkam Al-Quran by Al-Arabi - Sakhi Rehman; Safi Ullah; Professor Dr.Muhammad Aslam Khan (`, 2025)
This paper looks into the social problems as presented in Surah Nur by comparing two of the most important traditional exegeses; Ahkam al-Qur an by Al-Jassas (Hanafi school) and Ahkam al-Qur an by Ibn al-Arabi (Maliki school). Surah An-Nur is known to be a heavy legislative surah containing various provisions regarding ethical provisions, family life, modesty, chastity and all the limits of the public and the private life in the Islamic society. The purpose of the study is to find out how two scholars read the same verses in different ways and this reveals the plurality in legal and moral thought in Islamic jurisprudence. The thesis explores such key social issues as adultery and its punishment, the charge of unchastity, hijab (veil), and gender interaction, the marriage of chaste individuals, and the place of the community in upholding moral standards. Both scholars point out these problems yet use their legal approaches which are founded on the basis of their own madhhabs. To take an example, whereas Al-Jassas concentrates on legal technicality and juristic inferences based on Hanafi usul (principles), Ibn al-Arabi concentrates on maqasid (higher objectives) and the social implications of rulings in accordance with Maliki priorities. Further, the study throws light on the tale of al-Ifk (false allegation against Aisha R.A.) and how it reflects on the media ethics, social justice and how a news should be verified before being disseminated. It also explores the way both exegetes manage issues of privacy, domestic space (istidhan) and the institution of family that brings out a sophisticated interpretation of Islamic social order. Comparative approach will assist in showing the points upon which the two approaches are agreeing and disagreeing and the role of the historical, geographical, and methodological variables in conditioning their tafsir. By so doing, the research can be added to the academic discussion of tafsir al-ahkam and its applicability to modern ethical issues, i.e., to the problems of digital privacy, online defamation, and gender relations in the contemporary Muslim communities. Finally, this study has reached a conclusion that Surah An-Nur provides all-inclusive framework of creation of a morally upright society. Both Al-Jassas and Ibn al-Arabi testify that surah can be used in order to regulate individual behaviors and rectify society. The fact that they take different directions is not incompatible and instead complements the Islamic thought with varied understandings of how God reveals him or herself concerning the complex realities of human beings. Keywords: Surah An-Nur, Ahkam al-Quran, Al-Jassas, Ibn al-Arabi, Social Ethics in Islam, Comparative Tafsir, Islamic Legal Thought